Ultrafast co2 Photodissociation in the Energy Region of the Lowest Rydberg Series - Triana-Galvis, J (Royal Society of Chemistry, 2022)
We present a detailed theoretical survey of the electronic structure of excited states of the CO2 molecule, with the aim of providing a well-defined theoretical framework for the quantum dynamical studies at energies beyond 12 eV from the ground state. One of the major goals of our work is to emphasize the need for dealing with the presence of both molecular valence and Rydberg states. Although a CASSCF/MRCI approach can be used to appropriately describe the lowest-lying valence states, it becomes incapable of describing the upper electronic states due to the exceedingly large number of electronic excitations required. To circumvent this we employ instead the EOM-CCSD monoconfigurational method to describe the manifold of both valence and Rydberg states in the Franck-Condon region and then a matching procedure to connect these EOM-CCSD eigensolutions with those obtained from CASSCF/MRCI in the outer region, thus ensuring the correct asymptotic behavior. Within this hybrid level of theory, we then analyze the role of valence and Rydberg states in the dynamical mechanism of the photodissociation of quasi-linear CO2 into CO + O fragments, by considering a simple but effective 1D multistate non-adiabatic model for the ultrafast C-O bond break up. We show evidence that the metastability of the Rydberg states must be accounted for in the ultrafast dynamics since they produce changes in the photodissociation yields within the first tens of fs. © 2022 The Royal Society of Chemistry.